Triterpenoid saponins from the root of Weigela florida - Duc Hung Nguyen; Quang Tan Tu; Hoang Mau Chu (Vietnam Journal of Science, Technology and Engineering, 2022)
Plants belonging to the Weigela genus are traditionally used to flourish gardens, homes, and other living areas. This genus contains ten species that are mainly found in Asia, but many cultivars have been cultivated around the world. Previous studies on some species of this genus revealed the occurrence of triterpenoid saponins, which possess interesting biological activities such as cytotoxicity, anti-complementary activity, and anti-inflammatory activity. Based on this suggestion, a phytochemical study on the roots of W. florida “Jean's Gold” was carried out using different chromatographic methods, spectroscopic analysis in 1D- and 2D-NMR, and mass spectroscopic method (HRESI-MS in negative mode). The isolation of three known oleanane-type triterpenoid saponins was revealed as olean-12-en-28-oic acid, 3-[(O-β-D-xylopyranosyl-(1→4)-O-β-D-glucopyranosyl-(1→4)-O-β-D-xylopyranosyl- (1→3)-O-6-deoxy-α-L-mannopyranosyl-(1→2)-β-D-xylopyranosyl)oxy]-, (3β)- (compound 1), olean-12-en-28-oic acid, 3-[(O-β- D-xylopyranosyl-(1→4)-O-β-D-glucopyranosyl-(1→4)-O-β-D-xylopyranosyl-(1→3)-O-6-deoxy-α-L-rhamnopyranosyl-(1→2)- α-L-arabinopyranosyl)oxy]-, (3β)- (compound 2), and olean-12-en-28-oic acid, 3-[(O-α-L-arabinopyranosyl-(1→3)-O-[α-Lxylopyranosyl-(1→4)]-O-β-D-glucopyranosyl-(1→4)-O-β-D-xylopyranosyl-(1→3)-O-6-deoxy-α-L-rhamnopyranosyl-(1→2)-α-Larabinopyranosyl)oxy]-, (3β)- (compound 3). Full characterisation of the three saponins presented in this study gives a better understanding of the phytochemistry of ornamental plants, which can be used further for medicinal purposes.